1995
DOI: 10.1093/hmg/4.6.993
|View full text |Cite
|
Sign up to set email alerts
|

Circulating human factor IX produced in keratin promoter transgenic mice: a feasibility study for gene therapy of haemophilia B

Abstract: It has previously been suggested that keratinocytes might provide a suitable target cell for delivery of factor IX to the systemic circulation for gene therapy of haemophilia B. Here, an investigation of the use of cellular gene promoters specific for keratinocytes was undertaken to examine whether factor IX could be passed from the epidermis to the systemic circulation. Utilizing two bovine cytokeratin gene promoters, BKIII and BKVI, three lines of transgenic mice were generated with targeted expression of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…These animals died within several weeks after birth, making it impossible to assess the long-term potential for keratinocyte-derived K14-TNF-␣ to sustain high serum levels of the transgene product. The bovine K10 promoter, expressed in terminally differentiating keratinocytes, has also been used to produce and secrete high levels of circulatory factors in transgenic mice (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…These animals died within several weeks after birth, making it impossible to assess the long-term potential for keratinocyte-derived K14-TNF-␣ to sustain high serum levels of the transgene product. The bovine K10 promoter, expressed in terminally differentiating keratinocytes, has also been used to produce and secrete high levels of circulatory factors in transgenic mice (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Our study is the first to demonstrate that targeting to keratinocytes, using lipid-mediated transfection of plasmid constructs containing endogenous promoters as well as the expansion and subsequent grafting of these cells for gene therapy, is a feasible approach. Expression driven by regulatory sequences of genes coding for structural proteins such as keratins, involucrin or fillagrin ensures precise stratum localization and abundant production of the therapeutic protein.…”
Section: Figure 5 Immunoperoxidase Staining Of Blood Vessels In Graftmentioning
confidence: 92%
“…These and other transgenic data reinforce the concept that keratinocytes may act as a source of cytokines and/or therapeutic proteins that reach the underlying dermis or the bloodstream to exert biological action. 24,25 Ex vivo targeting of keratinocytes for gene therapy has been performed almost exclusively using retroviral vectors. [26][27][28][29][30][31] In spite of several advantages of this approach, in vivo maintenance of gene expression driven by the viral long terminal repeat (LTR) promoters has proved difficult for reasons not yet entirely understood.…”
Section: Correspondence: Jl Jorcano Project On Cell and Molecular Bimentioning
confidence: 99%
“…The acellular matrix was fixed in 4% glutaraldehyde for 1 h, washed extensively in phosphate-buffered saline followed by HaCaT medium overnight. The matrix was inverted and 5 × 10 5 MRC5 fibroblasts 35 were seeded on to the bottom surface, followed by 5 × 10 5 HaCaT cells on to the upper surface of the reverted matrix the following day. After 3 days in culture at the air-liquid interface, the 'hat-like' component of the transplantation chamber (Renner) was placed over the ring and the entire organotypic skin structure was embedded within a full thickness incision on the back of an 8-to 10-week-old male MF1 nu/nu mouse (Harlan Olac, Bicester, UK) on to granulation tissue pre-formed by the temporary implantation of a 13-mm glass disc (Renner) 2 weeks before skin grafting.…”
Section: Superficial Skin Grafting Of Hacat Cellsmentioning
confidence: 99%
“…3,4 The levels of protein detected in plasma after transduced cells are transplanted to animals are much lower than predictions based upon the high levels of gene expression observed in the same cells in culture. 2 This might be due to cell death or might be caused by a problem of transport to the plasma, although transgenic studies have shown that when factor IX 5 and human growth hormone 6 are placed under the transcriptional control of keratinocyte-specific regulatory elements, protein is detected in the plasma. Control experiments show that this is likely to be due to lymphatic drainage of the skin.…”
Section: Introductionmentioning
confidence: 99%